Enhanced Design of On-Chip Monopole Antenna Inspired by Partially Reflective Surface at 5.8 GHz - Ahmadu Girgiri; Mohd Fadzil Ain; Mohd Zamir Bin Pakhuruddin; Bello Abdullahi Muhammad; Abdullahi Sarkin Bauchi Mohammed (Advances in Technology Innovation, 2024)
The increasing popularity of compact, chip-based devices has spurred interest in developing on-chip antennas (OCAs). However, OCAs suffer from low gain and poor radiation efficiency due to the silicon substrate’s low resistivity and high permittivity, influencing antenna performance. To avert these challenges, this study aims to enhance an OCA’s gain and radiation efficiency by incorporating a partially reflective surface (PRS) into the antenna structure. The antenna is simulated using 3D CST software, and its performance is evaluated. To validate the simulation, an antenna prototype is fabricated using sputtering and chemical vapor deposition (CVD) technologies. The prototype demonstrates a peak gain of 2.14 dB and radiation efficiency of 72.2%, showing a 24.3% gain increase and a 16.25% efficiency increase compared to the design without PRS. Additionally, it achieves an impedance bandwidth of 0.63 GHz, making it suitable for WiMAX, RFIC, and Wi-Fi 6 applications.